Memaknai Persatuan dalam Kehidupan Multikultural sebagai Penangkal Radikalisme - Darul Lailatul Qomariyah (Tarbawi: Journal of Islamic Education, 2020)
Indonesia as a country that stands on cultural diversity requires the importance of multiculturalism in nation building. With this multiculturalism, the principle of "unity in diversity" as stated in the basis of the state will be realized. The cultural diversity possessed by the Indonesian people will be an inspiration and potential for national development so that the ideals to realize a just and prosperous of Indonesian society as stated in the opening of the 1945 Constitution can be achieved. Various concepts which are relevant to multiculturalism such as democracy, justice and law, cultural values ​​and ethos, togetherness in equal differences, ethnicity, ethnicity, ethnic culture, religious beliefs, religious expressions, cultural expressions, private and public domains, human rights , community cultural rights, and others. The emergence of the concept of multiculturalism is often associated with religion, namely "religious multiculturalism" which emphasizes the non-separation of religion from the state, does not tolerate the existence of understanding, culture, and people who are atheists (Harahap, 2008). In this context, multiculturalism is seen as an enrichment of the concept of religious harmony that is developed nationally. By embodying the right multicultural concept, it is believed that it can counteract the understanding of radicalism that can threaten the divisions of the Indonesian nation.